Targeting hyperosmolar therapy in pediatric traumatic brain injury - Maas, Andrew I. R. (Journal of Emergency and Critical Care Medicine, 2018)
In a recent issue of this Journal, Rallis et al. report on the effectiveness of 7.5% hypertonic saline (HTS) for the treatment of raised intracranial pressure (ICP) in children with severe traumatic brain injury (TBI) (1). This is a highly relevant and timely contribution. Across all ages, the incidence of TBI is highest in the age group 0–4 years. Data from the Centers for Disease Control (CDC) in the US show that US emergency department visits for TBI increased by 37.8% between 2007 and 2013 for the 0–4 years, to 1,592 cases per 100,000 people (2). The disease course in children with TBI can be very different from adults and is often characterized by substantial brain swelling causing raised ICP.